Sail me away home - LeZotte, Ann Clare (Scholastic Press, 2023)
Fourteen-year-old teacher, Mary Lambert, travels to Paris where she encounters a wellspring of formalized deaf education and sign language, but when she discovers the missionaries' questionable plan to "save" deaf children, she must decide if pursuing her goals is worth betraying her friends.